Analisa Bi-Variat Pengaruh Panjang Ruas Jalan Dan Volume Kendaraan (Lhr) Terhadap Tingkat Kecelakaan Di Jalan Tol Surabaya â Gempol Dan Jalan Tol Surabaya â Gresik - (Jurusan Teknik Sipil Politeknik Negeri Semarang), Nur Setiaji Pamungkas (Teknis, 2015)
Safety aspects to be important in the development of the transportation system. Different events occur on the road pushing the chances of conflict against the friction (friction). Addition of a vehicle rapidly and do not offset the availability of road infrastructure system for road transport has yet to provide an adequate service. The accident became one of the result of conditions that cannot be controlled. This research aims to know the influence of the length of the roads and the volume of the vehicle against the level of accident in Surabaya-Gresik toll road and the Surabaya-Gempol toll road. Used analysis of bi-variat (analysis of the relationship of two variables) with the help of the microsoft excel program to know the pattern of influence traffic volume and a long road towards the level of accidents on the freeway. The results of the analysis using excel shows that in general the pattern of the relationship between the level of accidents with the length and volume of road vehicle has a pattern like the letter U, but to the relationship between the level of accidents and the volume of vehicles in Surabaya-Gresik toll road that shows the pattern like the letter U upside down. Linear regression analysis of the results shows that a linear regression model is inappropriate to predict the relationship between level of accident-free varibel with volume of vehicles and long road in the Surabaya-Gempol toll road and toll roads in Surabaya-Gresik.Keywords: long road, highway, multiple linear regression, traffic volume, the rate of accidents